2020
DOI: 10.3389/fnmol.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile at the Motor Endplate of the Neuromuscular Junction of Fast-Twitch Muscle

Abstract: The neuromuscular junction (NMJ) is a prototypic chemical synapse between the spinal motor neuron and the motor endplate. Gene expression profiles of the motor endplate are not fully elucidated. Collagen Q (ColQ) is a collagenic tail subunit of asymmetric forms of acetylcholinesterase and is driven by two distinct promoters. pColQ1 is active throughout the slow-twitch muscle, whereas pColQ1a is active at the motor endplate of fast-twitch muscle. We made a transgenic mouse line that expresses nuclear localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…IP assays of HNSCC cells from K14CreER;RiboTag;Mettl1 fl/fl or K14CreER;RiboTag;Mettl1 wt/wt mice were performed as described previously [ 38 , 39 ]. Briefly, HNSCC tissues were mashed by a multisample tissue grinding machine (Jingxin, Xinchang, Zhejiang, China) in supplemental homogenization buffer.…”
Section: Methodsmentioning
confidence: 99%
“…IP assays of HNSCC cells from K14CreER;RiboTag;Mettl1 fl/fl or K14CreER;RiboTag;Mettl1 wt/wt mice were performed as described previously [ 38 , 39 ]. Briefly, HNSCC tissues were mashed by a multisample tissue grinding machine (Jingxin, Xinchang, Zhejiang, China) in supplemental homogenization buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The muscle and nerve samples were immediately frozen in isopentane, cooled with liquid nitrogen, and stored at −80°C. Immunohistochemical staining was performed as described elsewhere, with minor modifications 10–12 . Briefly, histological and immunohistochemical analyses were carried out on 8‐μm‐thick frozen sections prepared using a cryostat.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study were analysed and reported in accordance with the STROBE guidelines 8 . The real-time PCR test was performed as previously described with modification 9 , 10 , and was based on the criteria provided by the World Health Organization (WHO) 11 . Nasopharyngeal swabs were taken on the 1st, 7th and 14th days of medical isolation observation.…”
Section: Methodsmentioning
confidence: 99%